2017
DOI: 10.1097/jsm.0000000000000331
|View full text |Cite
|
Sign up to set email alerts
|

Preseason Aerobic Capacity Is an Independent Predictor of In-Season Injury in Collegiate Soccer Players

Abstract: Efforts to increase aerobic capacity and LBM among soccer players in the off-season may help reduce in-season injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 32 publications
1
30
1
Order By: Relevance
“…Numerous studies related to various elements of physical fitness have attempted to identify factors that contribute to injury and illness risk in young athletes, although not at the elite level. Typically, physical fitness tests encompass components such as cardiorespiratory endurance, muscular strength, flexibility tests, and functional movement tests . Prior research studies on the adult population have demonstrated an association between higher levels of aerobic fitness and decreased injury risk, whereas research on the relationship between physical fitness level and illness risk is limited and mostly focus on increasing training loads .…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies related to various elements of physical fitness have attempted to identify factors that contribute to injury and illness risk in young athletes, although not at the elite level. Typically, physical fitness tests encompass components such as cardiorespiratory endurance, muscular strength, flexibility tests, and functional movement tests . Prior research studies on the adult population have demonstrated an association between higher levels of aerobic fitness and decreased injury risk, whereas research on the relationship between physical fitness level and illness risk is limited and mostly focus on increasing training loads .…”
Section: Introductionmentioning
confidence: 99%
“…This is an interesting field for research, and some papers are finding results to corroborate this. [ 29 ] In this case, it reinforces the need to evaluate and improve the aerobic fitness of professional soccer players before they return to play, to avoid other injuries.…”
Section: Discussionmentioning
confidence: 86%
“…[ 24 ] Also, it has been demonstrated that VO 2max is an independent predictor of injury in soccer players. [ 29 ]…”
Section: Discussionmentioning
confidence: 99%
“…1 , 14 , 16 , 17 , 24 , 27 Whereas BMI is often used as an indirect measure of adiposity in the general public, the significant influence of muscle mass on BMI in high-level athletes may confound this relationship. Although a prior study of middle school and high school athletes from multiple sports found that injury risk increased with age, Watson et al 34 found that age was unrelated to in-season injury risk in a group of collegiate soccer athletes. We are aware of no prior research that has evaluated years of experience as a risk factor for injury in female youth athletes.…”
Section: Discussionmentioning
confidence: 95%
“…It was recently found that higher preseason fitness was associated with a decreased risk of in-season injury among male and female collegiate soccer players when measured directly as maximal aerobic capacity (VO 2max ). 34 Together, these findings suggest that off-season interventions in adult athletes to improve aerobic fitness may reduce in-season injury risk.…”
mentioning
confidence: 91%